Biomass assessment, volume equations and crown architecture of Eucalyptus pellita F. Muell in a commercial plantation in Mexico - Rodríguez-Solís, María (2015)
A fixed number of 6 trees from a provenance study were selected at random in a commercial plantation of Eucalyptus pellita, from different diameter classes. Each tree was separated by components: stem, leaves, branches, which were then weighed to obtain green weight. Linear regressions were carried out to obtain straight forward biomass models for the aerial component, using DBH as the independent variable. Later corresponding analyzes were performed to obtain the amount of carbon (C) and carbon dioxide (CO2) stored in a 2.5 year old plantation. Overall, we obtained an average of 27.04 kg of carbon stored in the stem and 10.44 kg of carbon in the foliage, which represents a reservoir of 99.23 kg of CO2 stored in the stem and 38.32 kg of CO2 in the foliage. In literature, not many studies are found on crown development; the present study relates crown height, crown diameter and total height into 4 indexes which describe a given structure of the tree (Crown Coverage (CC), Crown Index (CI), Crown Shape (CS), Crown Shade (CSd)). The results show, for the six sampled individuals, a relatively high value for CC, showing the lowest value for the smallest diameter; crown coverage indicates that the species at this age class is still growing rather exponentially and that its photosynthetic area needs still to be high to sustain such growth. Concerning crown shape index, the higher the diameter is, the higher the value becomes, which indicates that diameter growth can be related positively to CS; deducing a healthy crown development the higher this value becomes. The CSd values confirm this statement as the relationship is kept.